Observing students’ problem solving strategies in mechanics by eye-tracking method - Hejnová, Eva; Kekule, Martina (Scientia in educatione, 2018)
The paper is focused on observation of students’ problem solving strategies when solving concept cartoons tasks testing their understanding of the 1st and 2nd Newton’s law. Students’ solving process was recorded by an eye-tracker and, based on their tracked eyemovements, analysis of their approaches was provided. Students solved tasks from the R-FCI test as well. Detailed analysis of the solutions of four high-school students, one college student and one teacher was provided.